Exploring atmospheric free-radical chemistry in China: the self-cleansing capacity and the formation of secondary air pollution. Issue 3 (19th July 2018) - Lu, Keding; Guo, Song; Tan, Zhaofeng; Wang, Haichao; Shang, Dongjie; Liu, Yuhan; Li, Xin; Wu, Zhijun; Hu, Min; Zhang, Yuanhang
Abstract: Since 1971, it has been known that the atmospheric free radicals play a pivotal role in maintaining the oxidizing power of the troposphere. The existence of the oxidizing power is an important feature of the troposphere to remove primary air pollutants emitted from human beings as well as those from the biosphere. Nevertheless, serious secondary air-pollution incidents can take place due to fast oxidation of the primary pollutants. Elucidating the atmospheric free-radical chemistry is a demanding task in the field of atmospheric chemistry worldwide, which includes two kinds of work: first, the setup of reliable radical detection systems; second, integrated field studies that enable closure studies on the sources and sinks of targeted radicals such as OH and NO3 . In this review, we try to review the Chinese efforts to explore the atmospheric free-radical chemistry in such chemical complex environments and the possible link of this fast gas-phase oxidation with the fast formation of secondary air pollution in the city-cluster areas in China.